Christianity in Latin America - Prien, Hans-J̈urgen. (Religion in the Americas, 2013)
Winner of the 2013 Choice Outstanding Academic Title Award Christianity in Latin America provides a complete overview of more than 500 years of the history of Christianity in the 'New World'. This book specifically focuses on conquest, exploitation of slave- and forced labor, mission, the formation of the Catholic Church after the council of Trent, Inquisition, popular religiosity, and postcolonial state formation. Attention is also given to the emergence of Protestant immigrant and mission churches, modern forms of exploitation of indigenous and Afro-American workers, Catholic-Protestant antagonisms from the beginning of ecumenism, liberation theology, the proliferation of Pentecostal churches, and the military dictatorships in the second half of the 20th Century. The inclusion of German research in this book is an important asset to the Anglo-American research area, in which information is disclosed that was previously unavailable in English. This book will present the reader with required handbook material on the history of Christianity on the South American continent, based on a tremendous breadth of literature. During his years as Technical Director in Central America, the author studied Mesoamerican Indian Cultures as well as the social conditions of the impoverished sectors of the population. This book is a compilation of the author's extensive research while a lecturer of church history at the Theological Faculty of São Leopoldo (Brazil), as well as during visits to nearly all countries of Latin America, and as a visiting professor in Portugal, Brazil, Nicaragua, Cuba, Argentine and Peru. Thorough research was also completed while lecturing at the University of Cologne (Germany) on Iberian and Latin American History, as well as during his term as professorial chair of Richard Konetzke and Günter Kahle. This publication is an amalgamation of the knowledge and expertise the author gained during research from his entire career.